Geschlecht. Derrida e il sesso - Iula, Emanuele (Rassegna di teologia, 2025)
Referring to the Heideggerian etymology of Geschlecht, Derrida inaugurates a reflection on sexuality which is decentralized with respect to its usual meaning, focusing on the schlagen in which Geschlecht is rooted, a hitting that generates recognition. The most delicate point of the essay will consist in a transition from a phenomenology of the hitting to that of the open hand that gives.